Validity of a single lactate measure to predict fixed lactate thresholds in athletes. Issue 4 (16th February 2017) - Garcia-Tabar, Ibai; Llodio, Iñaki; Sánchez-Medina, Luis; Asiain, Xabier; Ibáñez, Javier; Gorostiaga, Esteban M.
ABSTRACT: This study aimed to validate the use of a single blood lactate concentration measure taken following a 12 km h −1 running stage (BLC12 ) to predict and monitor fixed blood lactate concentration (FBLC) thresholds. Three complementary studies were undertaken. Study I : the relationships between BLC12 and the running speeds at FBLC of 3 mmol L −1 (S3mM) and 4 mmol L −1 (S4mM) measured during a multistage running field test were examined in 136 elite athletes. Study II : data from 30 athletes tested one year apart were used to test the predictive capacity of the equations obtained in Study I. Study III : 80 athletes were tested before and after an intensified training period to examine whether training-induced changes in FBLC thresholds could be predicted and monitored by BLC12 . Study I : BLC12 was significantly ( P < 0.001) and inversely related to S3mM ( R 2 = 0.89) and S4mM ( R 2 = 0.95). Study II : prediction models yielded robust correlations between the estimated and measured FBLC thresholds ( r = 0.94–0.99; P < 0.001). Study III : estimated changes predicted actual training-induced changes in FBLC thresholds ( r = 0.81–0.91; P < 0.001). This study gives empirical support to use a single lactate measure during a sub-maximal running field test as a simple, low-cost and practical alternative to FBLC thresholds in athletes.